Diseño de una máquina para la limpieza y clasificación del tomate (2018)
The development of this project consists of the "Design of a machine for the cleaning and classification of tomato". It began by defining the cleaning and classification needs of the tomato, taking into consideration the technical specifications that correspond to this vegetable that is going to be treated in the cleaning and classification process, in this case tomate chonto y tomate larga vida.Finally, the manufacturing plans of the machine, installation and operation manuals, environmental impact analysis and a cost-benefit financial study against a commercial machine are elaborated